EVALUATING STOCK MARKET PERFORMANCE IN LIGHT OF TERRORISM: AN EMPIRICAL EVIDENCE FROM PAKISTAN - Zeeshan Rasheed; Muhammad Yasir (`, 2024)
This study investigated the effect of terrorism and other key macroeconomic indicators on stock market in Pakistan. Monthly dataset has been utilized for empirical analysis from January 2007 to December 2020. The empirical model consists of Karachi Stock Market 100 Index as outcome variable while terrorism, real effective exchange rate and three months’ treasury bills rate as explanatory variables. The study employed a few time series tests such as Augmented Dickey Fuller and Co-integration test as pre-estimation formalities of time series data. Due to different orders of integration, the application of Auto Regressive Distributed Lag approach depicted that terrorism and treasury bills rate have significant and negative influences whereas real effective exchange rate has positive and significant influence on Stock market in the short run as well as in the long run. This study suggests that the negative impacts of terrorism can be minimized by correct use of government policies against terrorism and army operations across the country. Govt. should keep lower rate of returns on short term treasury bills and should take into account those measures which can result in higher exchange rate to enhance stock market. Keywords: Terrorism, Stock market, Co-integration, Treasury bills, Exchange rate JEL: E44, E58, F31, F52, F21